2024
DOI: 10.1136/rmdopen-2023-004039
|View full text |Cite
|
Sign up to set email alerts
|

The HLA region in ANCA-associated vasculitis: characterisation of genetic associations in a Scandinavian patient population

Christian Lundtoft,
Ann Knight,
Jennifer R S Meadows
et al.

Abstract: ObjectiveThe antineutrophil cytoplasmic antibody (ANCA)-associated vasculitides (AAV) are inflammatory disorders with ANCA autoantibodies recognising either proteinase 3 (PR3-AAV) or myeloperoxidase (MPO-AAV). PR3-AAV and MPO-AAV have been associated with distinct loci in the human leucocyte antigen (HLA) region. While the association between MPO-AAV and HLA has been well characterised in East Asian populations where MPO-AAV is more common, studies in populations of European descent are limited. The aim of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
(77 reference statements)
0
0
0
Order By: Relevance
“…Genotypes of SNPs located in different genes involved in the function of the immune system have been evaluated as risk factors for susceptibility and clinical outcomes of AAV. Several authors studied the association of certain SNPs in the human leukocyte antigen (HLA) regions and found differences in frequency according to ANCA specificity (myeloperoxidase (MPO) or proteinase-3 (PR3)) [ 14 , 15 ]. Casal Moura et al found an association of rs351111, located in the PR3 gene, with a higher frequency of severe relapses in a cohort of 188 patients [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Genotypes of SNPs located in different genes involved in the function of the immune system have been evaluated as risk factors for susceptibility and clinical outcomes of AAV. Several authors studied the association of certain SNPs in the human leukocyte antigen (HLA) regions and found differences in frequency according to ANCA specificity (myeloperoxidase (MPO) or proteinase-3 (PR3)) [ 14 , 15 ]. Casal Moura et al found an association of rs351111, located in the PR3 gene, with a higher frequency of severe relapses in a cohort of 188 patients [ 16 ].…”
Section: Introductionmentioning
confidence: 99%